Validation of an IGF1 Screening Method for Retinopathy of Pre-maturity - Pérez-Muñuzuri, Alejandro; López-Suárez, Olalla; Mandiá-Rodríguez, Natalia; López-Sanguos, Carolina; Blanco-Teijeiro, María José; Couce, María Luz (Frontiers in Pediatrics, 2020)
Retinopathy of pre-maturity (ROP) is a retinal disease that causes arrest of vascularization of the retina and can result in retinal detachment and blindness. Current screening protocols may not be sufficiently accurate to identify all at-risk patients. The aim of this study is to validate a method for improved identification of newborns at risk of ROP. We conducted a prospective clinical trial of pre-term newborns <32 weeks of gestation and/or <1,500 g birth weight during a 6-year period in a tertiary care hospital. We applied our new method based on measurement of insulin-like growth factor 1 (IGF1) levels at 3 weeks of age and the presence of sepsis during the first 3 weeks of life. Our screening protocol allowed exclusion of 121 (79.1%) patients for whom American Academy of Pediatrics (AAP) guidelines recommended screening, had a negative predictive value of 100%, and correctly identified all patients with ROP. Following retrospective assessment of our data based on these findings, we propose further restriction of the current AAP indications for screening to <1,100 g and <28 weeks of gestation in order to improve diagnostic efficacy while ensuring optimal use of restriction of human and material resources.